2011
DOI: 10.1002/cpp.787
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Turkish Young Compensation Inventory

Abstract: The YCI is a self-report questionnaire consisting of 48 items that assess the schema compensation strategies. The Turkish YCI has acceptable levels of reliability and validity. The Turkish YCI is ready to be used in both schema therapy practice and research settings in Turkey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
1
11
0
2
Order By: Relevance
“…Each YCI item is rated on a 6-point Likert scale from 1 ('completely untrue of me') to 6 ('describes me perfectly'). The YCI has satisfactory validity and reliability (LuKaraosmanoglu et al, 2013;Sundag et al, 2018). The internal consistency of YCI in the current study was .88.…”
Section: Young Compensation Inventory (Yci)supporting
confidence: 49%
“…Each YCI item is rated on a 6-point Likert scale from 1 ('completely untrue of me') to 6 ('describes me perfectly'). The YCI has satisfactory validity and reliability (LuKaraosmanoglu et al, 2013;Sundag et al, 2018). The internal consistency of YCI in the current study was .88.…”
Section: Young Compensation Inventory (Yci)supporting
confidence: 49%
“…However, reliability for the subscales of the German version of the YCI was insufficient and a 19-dimensional factor structure could not be confirmed (Grutschpalk, 2009). There are different findings regarding the number of factors in previous research (Grutschpalk, 2009; Karaosmanoğlu et al, 2013; Luck et al, 2005). Karaosmanoğlu et al (2013) found that compensation styles were not specific to any given schema.…”
Section: Methodsmentioning
confidence: 89%
“…significant if we used a 35-item version of the YCI (Karaosmanoglu et al, 2013), a 17-item version of the YRAI-1 (Luck et al, 2005) and a 37-item version of the YPI (Sheffield et al, 2005). These shorter versions were highly correlated with the corresponding original versions of the questionnaires, indicating that they measure the same constructs (YCI: r (58) = .977; YRAI-1: r (58) = .909; YPI: r (58) = .951; all p < .001).…”
Section: Additional Analysesmentioning
confidence: 99%
“…Schema therapy (ST) was originally developed for people with severe personality pathology and combines experiential, cognitive-behavioral, psychodynamic and interpersonal techniques [50]. The concept of schema modes is central in current ST [51].…”
Section: Methodsmentioning
confidence: 99%